Current Concepts in the Management of Advanced Trigger Finger: A Critical Analysis Review. Issue 9 (September 2021) - Pompeu, Yuri; Aristega Almeida, Bryan; Kunze, Kyle; Altman, Emily; Fufa, Duretti T.
Abstract : While the majority of patients with trigger finger obtain excellent outcomes from nonoperative treatment or release of the A1 pulley, a subset of patients with advanced trigger finger, defined as trigger finger with loss of active or passive range of motion, may have incomplete symptom relief and warrant specific attention. Advanced trigger finger is more refractory to complete symptom resolution from corticosteroid injection, and particular attention should be paid to incomplete improvement of flexion contractures. Unlike simple trigger finger, the pathology in advanced trigger finger involves not only the A1 pulley but also the flexor tendon, including thickening and degeneration. Progression toward surgical intervention should not be delayed when nonoperative measures fail, and specific attention should be paid to persistent inability to achieve full extension following A1 pulley release. Facing substantial residual flexion contracture, reduction flexor tenoplasty and partial or complete resection of the superficialis tendon followed by hand therapy and splinting may be needed to allow patients to regain reliable full range of motion.